Legal Liability of Health Care Facilities for Leakage of Patient Electronic Medical Records - Adi Herisasono (Faculty of Law, Universitas Pekalongan, 2025)
Electronic medical record (EMR) data breaches have become an increasingly significant issue in healthcare, as the use of digital technology for patient data management rises. EMRs provide healthcare professionals with faster and more efficient access to patient information. However, this convenience also introduces the risk of data breaches, which could harm patients. This article aims to explore the legal responsibilities of healthcare facilities in managing EMR data breaches and the consequences resulting from such breaches. The research employs a qualitative approach and literature review, analyzing various legal regulations, legislation, and case studies of data breaches. The findings indicate that while legal protections exist, there are still significant challenges in implementing effective data security systems in healthcare facilities. Therefore, enhancing oversight, security systems, and legal awareness among stakeholders is essential to prevent data breaches that could cause significant harm to multiple parties.